Storage Management System Problem and Firefly Algorithm Solution - Atas, Kubilay; Yildirim, Tulay (IEEE, 2019)
Today, many black box problems can be solved with nature-inspired meta-heuristic algorithms. These algorithms are used frequently to solve problems such as Traveling Salesman Problem, Knapsack Problem, Graph Coloring and Vehicle Routing problems which have combinatorial difficulties. In this study, Storage Management System problem which is similar to Traveling Salesman Problem is introduced. In this problem, it is aimed to find the most appropriate sequence in order to complete the list of access and stock requests in a short time in a rack system having a platform that can move independently in horizontal and vertical positions. In the study, Firefly Algorithm is proposed to solve the Storage Management System problem. Discrete solution of Firefly Algorithm is used and functions such as distance and light intensity are adapted to the problem.
Keywords: Storage Management System Problem; Traveling Salesman Problem; Firefly Algorithm; Computer Science